Ultrasound-Assisted Extraction of Squalene and 2-Acetyl-1-Pyrroline from Pandan Leaf: The Effects of Drying Methods and Extraction Conditions - Yanfei Cheng; Tao Fei; Yuyi Liu; Shuai Chen; Zexin Wang; Yiran Han; Lu Wang; Congfa Li (Foods)
Pandan, a tropical crop, is rich in squalene (SQ), known for its antioxidant and hypoglycemic properties, and 2-acetyl-1-pyrroline (2-AP), which imparts a characteristic aroma. This study focuses on the extraction of the two bioactive compounds from Pandan leaves and investigates the effects of drying methods, extraction solvents, and conditions on the yield of SQ and 2-AP. Results show that hot air-dried Pandan leaves when extracted using the binary solvent system of ethanol and n-hexane (EH), yield higher SQ content while maintaining an adequate content of 2-AP. To further optimize the extraction process, a single-factor experiment was followed by optimization using Box–Behnken design (BBD) and response surface methodology (RSM). The optimal extraction conditions were determined as follows: ultrasound time of 60 min, a temperature of 50 °C, power of 300 W, and a solid-to-liquid ratio of 1:5 g/mL. Under these conditions, an SQ yield of 1229.98 ± 13.09 μg/DW 1 g Pandan leaves and a 2-AP yield of 80.72 ± 0.88 μg/DW 1 g Pandan leaves were achieved, representing increases of 3.30% and 9.82% compared to pre-optimization values. Additionally, the antioxidant activities of EH extracts were evaluated through various in vitro assays. The extracts demonstrated significant DPPH and ABTS free radical scavenging activity (12.46 μmol TE/g DW and 22.14 μmol TE/g DW, respectively), along with ferric and cupric ion reducing power (10.629 μmol TE/g DW and 14.275 μmol TE/g DW, respectively). The extracts also exhibited notable inhibitory effects on α-amylase and α-glucosidase. The findings suggest that these extracts are a promising natural source of antioxidants with potential applications in health and nutrition.